2002
DOI: 10.1116/1.1520548
|View full text |Cite
|
Sign up to set email alerts
|

Direct patterning of nanostructures by field-induced deposition from a scanning tunneling microscope tip

Abstract: The process of local-field-induced deposition on a surface facing a scanning tunneling microscope (STM) tip has been investigated for several tip-sample systems. Applying negative voltage pulses, atoms can be transferred from the STM tip to the surface and, for example, platinum dots and lines have been drawn on gold or silicon samples by this technique. In this latter case, a discussion is proposed on growth mechanisms involved in field-induced deposition processes on the basis of growth kinetics studies. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Material deposition has also been observed at short pulses on the order of 10 ns, but a small change in the amount of materials deposited is observed with a pulse duration larger than 10 ms, which may imply the existence of a sort of saturation mechanism. Houel et al 17 also reported that the dot diameter increases slightly with the set current and pulse duration for the range considered. Moreover, the number of pulses has been found to have no influence on the dot volume deposition as long as the dot has been successfully deposited in the first few pulses.…”
Section: Scanning Tunneling Microscope Lithographymentioning
confidence: 87%
See 2 more Smart Citations
“…Material deposition has also been observed at short pulses on the order of 10 ns, but a small change in the amount of materials deposited is observed with a pulse duration larger than 10 ms, which may imply the existence of a sort of saturation mechanism. Houel et al 17 also reported that the dot diameter increases slightly with the set current and pulse duration for the range considered. Moreover, the number of pulses has been found to have no influence on the dot volume deposition as long as the dot has been successfully deposited in the first few pulses.…”
Section: Scanning Tunneling Microscope Lithographymentioning
confidence: 87%
“…There is a threshold voltage for the direct deposition. As indicated by Mamin et al 16 and Houel et al, 17 the threshold voltage, normally a few volts, is mainly influenced by the materials of tip and target, the distance of the tip-target gap, the tip-target configuration, and polarity. Mamin et al 16 also discovered that a gold dot previously deposited can be removed by a subsequent pulse on the same location.…”
Section: Scanning Tunneling Microscope Lithographymentioning
confidence: 96%
See 1 more Smart Citation
“…Depositing metal nanodots from the STM tip has been extensively studied for fabricating electrodes and circuits for electronic devices. [9][10][11][12][13][14][15] Most previous research used field-induced fabrication of dots where, between the tip and the sample, a voltage pulse of more than a few volts was applied 9-14 or the bias voltage was ramped to induce a point contact. 15 These methods yielded dots with lateral diameters ranging from several to hundreds of nanometers.…”
mentioning
confidence: 99%
“…It should be noted that the nanodots created by the point contacts were much smaller than those fabricated using high voltages. [9][10][11][12][13][14] The distance of the approaching tip necessary for making the point contact was determined by monitoring the tunneling current. Figure 1͑b͒ shows tunneling current as a function of the z-piezo displacement ͑I-Z curve͒ for two different tips ͑curves A and B͒ when the tip apex atom transfer has occurred.…”
mentioning
confidence: 99%